Mitigation of Over-Indebtedness Risk in Online Lending: A Comparative Analysis of Regulatory Frameworks in China, Malaysia, and Thailand - Salman Abdullah; Yenny Eta Widyanti; Djumikasih Djumikasih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
The rise of defaults and over-indebtedness in online lending reflects failures in credit risk management, mainly due to weak lending limitations and an imbalance between platforms and borrowers. This raises legal protection concerns for debtors, as aggressive lending practices are not based on repayment ability. Therefore, imposing restrictions on online lending is crucial to mitigate risks of default and over-indebtedness, through measures like setting maximum loan limits, conducting proportional creditworthiness assessments, and reinforcing prudence in fintech regulations. This research adopts a normative juridical approach with statutory, conceptual, and comparative methods, focusing on China, Malaysia, and Thailand. The study aims to identify an ideal framework for online lending limits to combat defaults and over-indebtedness. Findings show Indonesia lacks sufficient regulation, especially in real-time integration of cross-platform credit data, enabling debt-cycling. Indonesia’s regulatory approach is reactive, while Malaysia’s is proactive. Law enforcement against illegal lending is weak, and debt relief mechanisms are underdeveloped, unlike China and Thailand, which have implemented lending limits and consumer protections. This research recommends a new legal framework integrating national credit reporting with